Accurate multiple input switching solution for static timing analysis - El-Kinawi, Khaled (AUC Knowledge Fountain, 2013)
Multiple Input switching is a problem in Static Timing Analysis of nanoscale electronics, which is ignored in the industry. The methods and techniques of Static Timing analysis are discussed. Effective capacitance technique is presented. The composite current model is described and examined. The Multiple Input switching problem is explored and analyzed. The history effect in Multiple Input switching is explained. The miller capacitance effect is illustrated. A number of solutions, present in the literature, are discussed. A simple and innovative solution for the Multiple Input switching problem is presented. The solution is verified using Spice and matlab. Experimental evidence is presented to show the effectiveness of the solution. Matlab is used to simulate the solution. An Algorithm for minimum and maximum delay analysis is elaborated.